The Dutch Citizen's Understanding and Perception of the Actors Involved in the Netherlands' COVID‐19 Pandemic Response: A Focus Group Study During the First Pandemic Wave - L. S. Kengne Kamga; A. C. G. Voordouw; M. C. De Vries; E. Belfroid; A. E. M. Brabers; J. D. De Jong; L. C. vanEck; M. P. G. Koopmans; A. Timen (Health Expectations, 2024)
ABSTRACT Introduction The COVID‐19 pandemic was a public health emergency (PHE) of unprecedented magnitude and impact. It provided the possibility to investigate the Dutch citizens' understanding and perception of the actors involved in the Dutch pandemic response as a PHE unfolded. Methods Three focus groups (FGs) were held with 16 Dutch citizens in June 2020. Citizens were recruited using the Dutch Health Care Consumer Panel. During the FGs, participants were asked to fill in a table with actors they thought were involved in the management of the COVID‐19 pandemic. They also received information on actors involved in Dutch outbreak responses. Then, the actors named and omitted by the participants were discussed. Results An analysis of the FGs suggests that the Dutch citizens participating in the study were not fully aware of the scope of actors involved in the Dutch COVID‐19 pandemic response. Some participants would have appreciated more information on the actors involved. This would help them have an informed opinion of the actors involved in the decision‐making process, and accept non‐pharmaceutical interventions implemented. Lastly, most participants recognised that they played a role in limiting the spread of the COVID‐19 pandemic. Yet, very few spontaneously mentioned themselves as actors within the COVID‐19 pandemic response. Conclusion This study suggests that early in the COVID‐19 pandemic, the Dutch citizens participating in this study's FG did not have a complete understanding of the scope of actors involved in the Dutch COVID‐19 pandemic response, or the potential role of the citizen. Future research can build on these results to explore the citizen's perception of their role during PHEs of another origin, as well as other geographical and historical contexts. Patient or Public Contribution The public participated in the focus groups and received a non‐expert report summarising the outcomes of the focus groups.